2010
DOI: 10.1136/bjo.2010.182402
|View full text |Cite
|
Sign up to set email alerts
|

Serum vascular endothelial growth factor (VEGF) levels correlate with number and location of micrometastases in a murine model of uveal melanoma

Abstract: BackgroundA preliminary animal study was performed to determine if hepatic micrometastases from uveal melanoma secrete vascular endothelial growth factor (VEGF) that is measurable in serum.MethodsWe analysed the serum of a C57Bl/6 mouse model of uveal melanoma (n=10) at days 4, 7, 14 and 21 post-inoculation for VEGF levels. We compared the serum VEGF levels with the number and location of hepatic micrometastases and their respective expression of VEGF mRNA.ResultsSerum VEGF levels rose after inoculation of C57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 18 publications
2
16
0
2
Order By: Relevance
“…El-Shabrawi et al have shown that MMP-9 is predominantly expressed in highly aggressive uveal melanoma cells (32). A recent report showed that high level of VEGFA was correlated with the number and location of micrometastases in a murine model of uveal melanoma (33). In this study, we observed that MMP-2, MMP-9, and VEGFA altered in the same pattern as NF-κB1.…”
Section: Discussionsupporting
confidence: 66%
“…El-Shabrawi et al have shown that MMP-9 is predominantly expressed in highly aggressive uveal melanoma cells (32). A recent report showed that high level of VEGFA was correlated with the number and location of micrometastases in a murine model of uveal melanoma (33). In this study, we observed that MMP-2, MMP-9, and VEGFA altered in the same pattern as NF-κB1.…”
Section: Discussionsupporting
confidence: 66%
“…The need for blood biomarkers for uveal melanoma has become more—and not less—urgent in the era of the molecular prognostication. The work reported by Crosby et al 3 provides support to those involved in this important effort.…”
mentioning
confidence: 66%
“…VEGF production by tumours and cells in the tumour environment is a critical step in the formation and progression of metastasis 3. Foremost is that the serum VEGF levels are measurable when liver metastases are microscopic, suggesting that testing may have the requisite sensitivity.…”
mentioning
confidence: 99%
“…Currently, there are limited studies in the literature investigating VEGF-A expression in UM, and fewer assessing the inhibition of this cytokine in animal models, thus comprehensive studies regarding VEGF-A in multiple UM cell lines are needed [25, 26, 29, 40]. In the present study, we determined that three UM cell lines produced copious amounts of VEGF-A (between 4600 and 12,000 pg/μL).…”
Section: Discussionmentioning
confidence: 78%
“…In vitro studies have also revealed that UM cell lines produce VEGF-A in normal culture and production increases under hypoxic conditions [23, 24]. Furthermore, in an animal model of UM, increased VEGF-A levels were detectable in serum, and these escalations correlate with increased metastasis [25]. Reports vary with regard to VEGF-A positivity in primary UM tumours, ranging from 22% to 84%, and there are conflicting reports regarding correlations between expression levels and tumour size, vascularisation, or metastasis [26, 27].…”
Section: Introductionmentioning
confidence: 99%